RITME EDITING UNTUK MEMPERKUAT DRAMATIK - Pitaloka, Canda; Sasongko, Hery; Andela, Jhori (Institut Seni Indonesia Padangpanjang, 2024)
The fictional film Katresnan is a family drama genre film, this film is based on the phenomenon of a family between parents, children and in-laws which causes the child to be depressedover two choices. This fictional film tells the story of a girl named Hayatri who has just married and asks her parents for permission to move house with her husband. However, it was not the blessing that Hayatri received, but a threat fiven by his parents to Hayatri to cancel his plans to move due to the weton problem which did not match the placement of he house. The concept applied is editing rhythm to strengthen the drama of the main character in dealing with conflict. The result of the application of rhythm editing in the fictional film Katresnan are slow rhythm and fast rhythm. Slow rhythm are applied to scene that build the sad and sad atmosphere of the main character which aims to provide dramatic pressure. Fast rhythms are applied when to strengthen emitions, be sensitive and increase the tension in the scene. The rhythm is presented throught shot duration and shot selection. Slow editing rhythm will use fewer cuts moving shots, while fast editing rhythms will use a larger number of shots.